Attainment of Nitrogen Solubility, Characteristic Study and its Effects on Martensitic Stainless Steel using Conventional Method of Melting in as Cast Condition - Valasamudram, V; Anburaj, J (International Journal of Engineering and Technology, 2018)
Steels ruled the world for the past two century owing to the carbon as an interstitial element, due to corrosion and less toughness on hard phases like martensite, was in a need to develop the corrosion resistive with more hardness without compromising toughness is in martensitic steel using nitrogen as interstitial in spite of carbon. Though the many technologies available to produces nitrogen-alloyed steel, due to cost effectiveness and process complication conventional method is chosen. Through conventional melting achieved nitrogen solubility in melts M1, M3, M5, M9, M10, M11 as 0.510 to 0.992 in volume fraction. This result has validated with theoretical nitrogen solubility using Sievert's law.Â Nitrogen solubility got above 1.02 to 1.35 of volume fractions in few melts, found porosity/ gas holes as confirmed by Simmons (1996). The hardness test and microstructure also reveals that the performance of the nitrogen solubility in hardness as-cast condition. The hardness is 341 to 472 HV, in this M10 is the highest of 472 HV hardness in as-cast condition concerning the nitrogen solubility of 0.973 M3 shows 341 is due to low Cr The microstructure also influence the hardness in decreases is due to higher percentage content of ferrite and also hardness increases is due to the attributed network of ferrite and alloy carbides.